2003
DOI: 10.1007/s00234-002-0935-3
|View full text |Cite
|
Sign up to set email alerts
|

A functional MRI study of somatotopic representation of somatosensory stimulation in the cerebellum

Abstract: Somatotopic representation in the cerebral cortex of somatosensory stimulation has been widely reported, but that in the cerebellum has not. We investigated the latter in the human cerebellum by functional MRI (fMRI). Using a 1.5 tesla imager, we obtained multislice blood oxygen level-dependent fMRI with single-shot gradient-echo echoplanar imaging in seven right-handed volunteers during electrical stimulation of the left index finger and big toe. In the anterior and posterior cerebellum, activated pixels for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 13 publications
8
21
0
Order By: Relevance
“…A study using electrical stimulation of the lower extremities [Smith et al, 2003], reported that afferent spinocerebellar information from muscle, joint and tactile receptors is important for the preparation and correction of ongoing movement. Takanashi et al [2003], using also electrical stimulation demonstrated a similar somatotopical organization within the cerebellum. We conclude that the observed cerebellar activation pattern in our study has been elicited by the passive movement, as well as by the electrical stimulation itself.…”
Section: Figurementioning
confidence: 69%
“…A study using electrical stimulation of the lower extremities [Smith et al, 2003], reported that afferent spinocerebellar information from muscle, joint and tactile receptors is important for the preparation and correction of ongoing movement. Takanashi et al [2003], using also electrical stimulation demonstrated a similar somatotopical organization within the cerebellum. We conclude that the observed cerebellar activation pattern in our study has been elicited by the passive movement, as well as by the electrical stimulation itself.…”
Section: Figurementioning
confidence: 69%
“…30.2; Nitschke et al 1996;Bushara et al 2001;Grodd et al 2001Grodd et al , 2005; see also Takanashi et al 2003;Thickbroom et al 2003). The upside-down somatotopic representation in the anterior lobe has been confirmed in humans: leg and foot sensorimotor representations are localized to lobules II and III (Nitschke et al 1996), hand representations are in lobule V (e.g., Bushara et al 2001;Grodd et al 2001), and orofacial movements activate medial regions of lobule VI (Urban et al 2003;Dresel et al 2005).…”
Section: Activation During Sensorimotor Tasksmentioning
confidence: 84%
“…A previous study using lower extremity electrical stimulation indicated that afferent spinocerebellar information from muscles, joints, and tactile receptors is important for the preparation and correction of ongoing movement [22]. Takanashi et al [23] also demonstrated a similar somatotopical organization within the cerebellum after electrical stimulation. It is conceivable that the cerebellar activation pattern observed in the present study was elicited by passive movement, as well as by the electrical stimulation itself.…”
Section: Discussionmentioning
confidence: 98%